Solution-focused group counseling: A solution to enhance students’ self-confidence - Jahara, Aini; Daulay, Nurussakinah (Universitas Islam Negeri Raden Intan Lampung, 2023)
Self-confidence plays a pivotal role in developing an individual’s potentials. Solution-focused counseling approach views an individual as the only expert for his/her own life, and only they themselves are capable of making the best decision. This study aimed to assess the effectiveness of solution-focused group counseling sessions in enhancing students' self-confidence. To this end, a pretest-posttest control group experimental study was conducted, involving twelve students of Public Islamic Senior High School 3 Langkat, who were assigned into two groups of six participants each. Data collected from self-confidence scale were analyzed using Wilcoxon Sign Test by identifying the difference in average improvement of self-confidence. The experimental group exhibited a significance value of 0.002 (< 0.005), indicating that the solution-focused group counseling could improve students’ self-confidence.